Obatoclax as a perpetrator in drug-drug interactions and its efficacy in multidrug resistance cell lines - Theile, Dirk; Allendorf, David; Köhler, Bruno Christian; Jassowicz, Adam; Weiß, Johanna (Journal of pharmacy and pharmacology, 2015)
Objectives Obatoclax is a pan-Bcl-2 inhibitor with promising efficacy, especially when combined with other antineoplastic agents. Pharmacokinetic drug-drug interactions can occur systemically and at the level of the tumour cell. Thus, this study scrutinised the interaction potential of obatoclax in vitro. Methods Obatoclax was screened for P-gp inhibition by calcein assay, for breast cancer resistance protein (BCRP) inhibition by pheophorbide A assay and for inhibition of cytochrome P450 isoenzymes (CYPs) by commercial kits. Induction of mRNA of drug-metabolising enzymes and drug transporters was quantified in LS180 cells via real-time polymerase chain reaction and involvement of nuclear receptors was assessed by reporter gene assays. Proliferation assays were used to assess whether obatoclax retains its efficacy in cell lines overexpressing BCRP, P-glycoprotein (P-gp) or multidrug resistance-associated protein 2 (MRP2). Key findings Obatoclax induced the mRNA expression of several genes (e.g. CYP1A1, CYP1A2 and ABCG2 (five to seven-fold) through activation of the aryl hydrocarbon receptor in the nanomolar range. Obatoclax inhibits P-gp, BCRP and some CYPs at concentrations exceeding plasma levels. P-gp, MPR2 or BCRP overexpression did not influence the efficacy of obatoclax. Conclusions Obatoclax retains its efficacy in cells overexpressing P-gp, MRP2 or BCRP and might act as a perpetrator drug in interactions with drugs, for example being substrates of CYP1A2 or BCRP.
Gesehen am 30.06.2020